Addressing research capacity for health equity and the social determinants of health in three African countries: the INTREC programme - Hofman, Karen; Blomstedt, Yulia; Addei, Sheila; Kalage, Rose; Maredza, Mandy; Sankoh, Osman A.; Bangha, Martin; Kahn, Kathleen; Becher, Heiko; Haafkens, Joke; Kinsman, John (Global health action, 2013)
BackgroundThe importance of tackling economic, social and health-related inequities is increasingly accepted as a core concern for the post-Millennium Development Goal framework. However, there is a global dearth of high-quality, policy-relevant and actionable data on inequities within populations, which means that development solutions seldom focus on the people who need them most. INTREC (INDEPTH Training and Research Centres of Excellence) was established with this concern in mind. It aims to provide training for researchers from the INDEPTH network on associations between health inequities, the social determinants of health (SDH), and health outcomes, and on presenting their findings in a usable form to policy makers.ObjectiveAs part of a baseline situation analysis for INTREC, this paper assesses the current status of SDH training in three of the African INTREC countries - Ghana, Tanzania, and South Africa - as well as the gaps, barriers, and opportunities for training.MethodsSDH-related courses from the three countries were identified through personal knowledge of the researchers, supplemented by snowballing and online searches. Interviews were also conducted with, among others, academics engaged in SDH and public health training in order to provide context and complementary material. Information regarding access to the Internet, as a possible INTREC teaching medium, was gathered in each country through online searches.ResultsSDH-relevant training is available, but 1) the number of places available for students is limited; 2) the training tends to be public-health-oriented rather than inclusive of the broader, multi-sectoral issues associated with SDH; and 3) insufficient funding places limitations on both students and on the training institutions themselves, thereby affecting participation and quality. We also identified rapidly expanding Internet connectivity in all three countries, which opens up opportunities for e-learning on SDH, though the current quality of the Internet services remains mixed.ConclusionsSDH training is currently in short supply, and there is a clear role for INTREC to contribute to the training of a critical mass of African researchers on the topic. This work will be accomplished most effectively by building on pre-existing networks, institutions, and methods.
Gesehen am 13.07.2021